Evaluasi Risiko Keterlambatan Pekerjaan Pembangunan Apron Baru Bandara Sultan Syarif Kasim II, Pekanbaru - Syifa Yulita; Ari Sandhyavitri; Alfian Malik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Implementation of the project of New Apron Development Workshop of Sultan Syarif Kasim II Airport, Pekanbaru from initial observations of previous authors poses a risk during the construction period of unpredictable events by civil engineer is a force majure condition such as unpredictable volume during interim planning The time set does not include unexpected or over volume work. The delay that occurred in the project of Advanced Construction Work of New Apron Sultan Syarif Kasim II Airport, Pekanbaru on the field is 228 days (planned for 322 days but the realization in field 550 days). This resulted in the late apron at the SSK airport to be usable. However, by carrying out risk analysis, mitigation and control procedure obtained the following results: for the probability of 80% delay in execution time to 68 days. Reduction time delay reaches 70%. Implementation of risk management can control the project risk systematically.Keyword: Risk analysis, delay, project, probability.